2003
DOI: 10.1046/j.1524-4725.2003.29195.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Porocarcinoma From Pre-existing Hidroacanthoma Simplex: Need of Early Excision for Hidroacanthoma Simplex?

Abstract: There was no recurrence for 72 months after wide excision. CONCLUSION. : We recommend an early excision and careful attention in the case of HAS because of its potential malignant change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
0
14
1
1
Order By: Relevance
“…The gross appearance of malignant HAS tended to vary, and there were nodular lesions or keratotic plaques with or without erosion and/or ulceration. [4][5][6][7][8][9][10][11] In the present case, the porocarcinoma portion was erosive with depigmentation, and such a case has been reported previously. 3 Therefore, clinical findings such as erosion and/or ulceration and depigmentation might be indicative of the malignant transformation of HAS.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The gross appearance of malignant HAS tended to vary, and there were nodular lesions or keratotic plaques with or without erosion and/or ulceration. [4][5][6][7][8][9][10][11] In the present case, the porocarcinoma portion was erosive with depigmentation, and such a case has been reported previously. 3 Therefore, clinical findings such as erosion and/or ulceration and depigmentation might be indicative of the malignant transformation of HAS.…”
Section: Discussionmentioning
confidence: 57%
“…12 Malignant variants of HAS are rare and have been reported under different names, such as malignant HAS, in situ porocarcinoma, eccrine porocarcinoma, and HAS with invasive growth. [2][3][4][5][6][7][8][9][10][11] Most cases developed from pre-existing benign HAS, 3,5,7,11 as did our present case. In a review of the literature on malignant HAS, 6 the ages of patients ranged from 50 to 87 years, with the majority of patients being over 70 years of age.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Although it has been suggested that the course of most HS lesions is benign [8], some have been thought to have potential for malignant transformation [9,10]. An observation of atypical cells and mitotic cells in tumor nests, suggesting malignant transformation, was reported in 7 (10%) of 70 cases.…”
mentioning
confidence: 99%
“…Mitoz ve tümör kalınlığının prognostik önemi bulunmadığını bildiren araştırıcılar da vardır (20). Duktal diferansiyasyon alanları CEA ve EMA immunohistokimyaları ile gösterilebilir (4,5,21). S100 ile neoplastik hücreler negatift ir (21,22,23).…”
Section: Discussionunclassified